Single Dose of Oral Dexamethasone and Multiple Doses Prednisolone in Treatment of Acute Exacerbations of Asthma - Tahir, Muhammad Umair; Zafar, Sadia; Farooqi, Muhammad Irfan; Tahir, Hassan (Indus Journal of Bioscience Research, 2025)
Background: Asthma is the most common chronic illness among children and a leading cause of emergency department visits. Systemic corticosteroids like prednisolone and dexamethasone are used for acute asthma exacerbations, but compliance and relapse remain concerns due to multi-dose regimens and side effects. Objectives: This study compared the efficacy of a single oral dose of dexamethasone to multiple doses of prednisolone for treating acute asthma exacerbations in children. Study Settings: Department of Pediatrics, Allied Hospital, Faisalabad. Duration of Study: Six months from 10 April 2024 to 10 October 2024. Data Collection: A randomized controlled trial involving 250 children aged 2–12 years with acute asthma exacerbations. Group A received a single dose of dexamethasone (0.6 mg/kg), and Group B received prednisolone (2 mg/kg/day for five days). Outcomes were monitored for relapse within seven days and efficacy was defined as no recurrent exacerbations during this period. Data analysis included chi-square tests and stratification by demographic and clinical variables. Results: Dexamethasone showed significantly higher efficacy (77.6%) compared to prednisolone (66.4%) (p=0.049). Stratified analysis highlighted dexamethasone's effectiveness in children with symptoms lasting 1–4 weeks (p=0.023) and in those presenting with “other symptoms” (p=0.019). No significant differences were observed by age, gender, or family history. Conclusion: Single-dose oral dexamethasone is a practical and effective alternative to multi-dose prednisolone for managing acute asthma exacerbations in children. It improves compliance and reduces relapse rates. Further research with larger sample sizes and longer follow-up is recommended to assess long-term outcomes and safety.